Thrombocytopenia as a Marker of Patient Outcome in Medical Intensive Care Unit - Abbas Fadae; Seyed Mojtaba Heidari; Maryam Alizadeh Chamkhaleh; Mohammad Amin Abbasi (International Journal of Cardiovascular Practice, 2018)
Introduction: Thrombocytopenia is a common hematologic disorder observed in many pathological conditions in critically ill patients. The current study aimed at investigating the prevalence of thrombocytopenia and its relationship with the length of stay and mortality among intensive care unit (ICU) patients.Methods: The current prospective cohort study enrolled 150 patients consecutively admitted to the medical ICU during a nine-month period. Patients’ baseline characteristics and underlying diseases were recorded. Laboratory findings and admission mean platelets and platelet counts on the 3rd day of admission were obtained. Patients were divided into thrombocytopenic (platelet count of less than 150×109/L or decrease of platelet to more than 50%) and non-thrombocytopenic groups according to the 3rd day platelet count.Results: Thrombocytopenia was detected in 53(35%) patients while 13 patients (8.6%) had severe thrombocytopenia (platelets count < 50 × 109/L). ICU stay and mortality were significantly higher in patients with thrombocytopenia compared with non-thrombocytopenic patients (16 ± 2.7 vs 12 ± 2.4 days, P = 0.01) and (45.5% vs 37.3%, P = 00.1) respectively.Conclusions: Platelet might be considered as a prognosis monitor in ICU settings. Severe thrombocytopenia could be mentioned as a poor prognostic factor for increased mortality and prolonged hospitalization period in ICU patients.